Synthetic skin. - Leventon, W. (IEEE spectrum)
Biomedical science has made a lot of progress in understanding how cells grow into functioning tissue and what chemical and other cues they need to do it right. Tissue engineering is the application of that knowledge to the building or repairing of organs, including skin, the largest organ in the body. Generally, engineered tissue is a combination of living cells and a support structure called a scaffold. The scaffold, depending on the organ in production, can be anything from a matrix of collagen, a structural protein, to synthetic biodegradable plastic laced with chemicals that stimulate cell growth and multiplication. The "seed" cells that initiate this propagation come from laboratory cultures or from the patient's own body. For future ventures to succeed, precise sensors and control systems will be needed to create and maintain the biochemical and mechanical environments that nurture tissues like skin. Also, robotics and other automation will be needed to remove people from the tissue growth process. Already, fledgling firms and tissue engineering labs are borrowing some advanced engineering practices, like high-precision rapid prototyping and photolithography, as they strive to create engineered bone, cartilage, blood vessels, and internal organs.